Summary of 8th IWGT in Ottawa, Canada - Martus, H. J.; Beevers, C.; Dertinger, S.; Froetschl, R.; Godschalk, R.; Gollapudi, B.; Hashimoto, K.; Kirkland, D.; Libertini, S.; Luijten, M.; McGovern, T.; Sugiyama, K.; et al. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
The International Workshops on Genotoxicity Testing (IWGT) are convened approximately every four years to bring together experts in the field of genetic toxicology; they are usually held as satellite meetings to the International Conference on Environmental Mutagens (ICEM). Working Groups (WGs), consisting of experts from industry, regional health authorities and academia are charged with providing consensus recommendations on contemporary issues in genetic toxicology; they reflect the state of the science for each topic. At the 8th IWGT, held in Ottawa, Canada, the following five WGs were formed: Statistical Approaches and Data Interpretation, chaired by Stephen Dertinger, USA Predictivity of In Vitro Genotoxicity Testing, a Mathematical Modelling Approach, chaired by Mirjam Luijten, The Netherlands Transcriptomic Biomarkers, chaired by Roland Froetschl, Germany In Vivo Strategies, chaired by Carol Beevers, UK Dose-response Analysis for Potency Comparisons and Risk Assessment, chaired by Paul White, Canada In addition, two plenary sessions critically discussed: Epigenotoxicity, chaired by Roger Godschalk, The Netherlands Gene Therapy, chaired by Silvana Libertini, Switzerland The products of each of the WG discussions, which are preceded by extensive analysis of available information, are one or several publications built around the consensus statements on each of the topics. These consensus statements focus on regulatory applications of the technology or topic(s) under discussion; thus, direct interpretation in a regulatory context is facilitated. For the podium discussions, reviews will be published to describe various aspects of the field and the state of the science. In the current session, presentations will be given on three of the WG topics (i.e., Statistical Approaches, Predictivity of In Vitro Testing, and In vivo Strategies). Summaries of the discussion outcomes and consensus statements of the other activities will also be presented.